Project-Based Learning for the Design of Progressive Dies Supporting Tools - Hakim, Rahman; Widiastuti, Hanifah; Wijayanti, Ita; Muvariz, Mufti Fathonah; Silaban, Andre Kevil (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Brawijaya, 2021)
In the oil and gas industry, manufacturing processes covered a variety of fields including pipe fittings production. Generally, this process involves a press machine utilized as a shape forming using punch-dies sets as mold profiles. The common problem found with the dies is the dimension of dies is not ergonomics to be handled manually by operators. Additionally, the support of dies tends to experience buckling upon receiving a pressure load of 15 MPa. Hence, alternative and practical designs are required, which have low deflection values and high fatigue resistance rates. Additionally, the designs are expected to be safe and economical. In this study, two alternative designs of punch-dies support are proposed. Subsequently, the FEA simulation was carried out for pipe fittings of 8 inches with ASME B16.9 standard size for WF Beam A36 Steel to compare the two proposed designs. The results show that alternative design 2 has a lower deflection value of 0.181 mm, a higher Factor of Safety of 3.21, and a higher cycle time of 358569 cycles than alternative design 1. Nevertheless, alternative design 2 has a higher production cost of 220 USD compared to alternative design 2. Therefore, this study shows that alternative design 2 has better performance while alternative design 1 is more economical.